Pengaruh Pemberian Insentif dan Pengalaman Kerja terhadap Kinerja Pegawai pada Politeknik Pelayaran Barombong - Masyita, Sitti; Wulandari, Usna (Insan Cita Bongaya Research Journal, 2023)
This research was conducted at the Barombong Shipping Polytechnic. The address is Jalan Permandian Alam No.1, Barombong, Tamalate District, Makassar City, South Sulawesi 90225. The research time is planned to be approximately 2 months. The population in this study were civil servants at the Barombong Shipping Polytechnic with a total of 105 civil servants. So the sample size required in this research is 51 respondents. From the output results carried out in the first hypothesis, it can be concluded that giving incentives does not have a significant effect on employee performance. This means that providing incentives is not a measuring tool that can improve employee performance. 2. From the results of the regression test carried out on the second hypothesis, it can be concluded that work experience has a positive and significant effect on employee performance. This means that the better an employee's work experience will influence the employee's performance and will provide positive things to the agency. 3. From the results of the regression test carried out on the third hypothesis, it can be concluded that providing incentives and work experience simultaneously influence employee performance. This means that the provision of incentives and the work experience that employees have will influence employee performance and the better their performance will be and will improve employee performance